RA05.06: CHANGES IN SKELETAL MUSCLE AND PHYSICAL FUNCTION AFTER ESOPHAGECTOMY: PROSPECTIVE SINGLE-CENTER COHORT STUDY. (14th September 2018) - Nishigori, Tatsuto; Tsunoda, Shigeru; Obama, Kazutaka; Kobayashi, Ami; Nobori, Yukiko; Hisamori, Shigeo; Hashimoto, Kyoichi; Itatani, Yoshiro; Tashiro, Naohiro; Shide, Kenichiro; Inagaki, Nobuya; Sakai, Yoshiharu
Abstract: Background: Sarcopenia (loss of muscle mass) has been shown to be associated with postoperative outcomes following esophagectomy. However, the impact of esophagectomy on postoperative muscle mass and function remains unclear. The prospective study aimed to evaluate the change in muscle mass and physical function after esophagectomy in sarcopenic patients in comparison with nonsarcopenic patients. Methods: The subject of the study was patients with cStage I-III primary esophageal cancer who were scheduled to undergo curative esophagectomy. Sarcopenia was diagnosed by measuring preoperative muscle mass with bioelectrical impedance analysis. Physical function was evaluated by measuring grip strength and walking speed. Postoperative muscle mass and function were evaluated between 1 and 3 months after surgery. Perioperative changes in muscle mass and function were compared between patients with and without sarcopenia Results: Among all 71 enrolled patients, 30 (41%) had sarcopenia. Sarcopenic patients had significantly lower muscle strength (34 vs 41 kg in male, 21 vs 26 kg in female) and a higher rate of postoperative complications (Clavien-Dindo grade 2 or higher, 77% vs 49%, P  = 0.018) compared to nonsarcopenic patients. Sarcopenic patients had a trend to lose greater amount of grip strength (-10.0% vs -5.6%, P  = 0.10) and walking speed (-8.2% vs -1.1%, P  = 0.18), while muscle mass decreased generally in both sarcopenic and nonsarcopenic patients (-8.0% vs -6.8%, P  = 0.46). Conclusion: Sarcopenic patients had a higher risk of postoperative complication and may lose further physical function following esophagectomy. Perioperative interventions such as nutrition exercise therapy should be considered for sarcopenic patients. Disclosure: All authors have declared no conflicts of interest.